Effect of xanthan gum-based food thickeners on the dissolution profile of fluoroquinolones oral formulations - Nobuyuki Takahashi; Yoshiaki Fujita; Nanako Takahashi; Akihiro Nakamura; Tsutomu Harada (BMC, 2020)
Abstract Background Xanthan gum-based food thickeners (XG-FTs) are often ingested by patients with dysphagia to prevent aspiration during drug treatment. Reportedly, XG-FTs affect tablet disintegration, drug dissolution rates, and reduce the efficacy of postprandial antihyperglycemic agents. The absorption rate and quantity of fluoroquinolone antimicrobial agents correlate with drug efficacy, raising concern about the impact of XG-FTs. Previously, we reported that film-coated tablets were less susceptible to the effects of XG-FT than conventional and orally disintegrating tablets. Here, we compare the effect of XG-FTs on dissolution profiles of three oral fluoroquinolone-based film-coated tablets by evaluating the dissolution of crushed products, fine granules, and film-coated fine granules. Methods We examined formulations of tosufloxacin tosylate monohydrate (TFLX), levofloxacin hemihydrate (LVFX), and ciprofloxacin hydrochloride hydrate (CPFX). The formulations were immersed in 20 mL of 1.5% (w/v) XG-FT aqueous solution for 2.5 min followed by a dissolution test using the paddle method according to the Japanese Pharmacopoeia (dissolution test solution pH 1.2; volume 900 mL; temperature 37 ± 0.5 °C). The dissolution profile was evaluated according to the dissolution quantity indicated in product specifications and guidelines for bioequivalence testing of generic drugs. The 15-min mean dissolution rate was determined for a formulation immersed in 1.5% (w/v) XG-FT aqueous solution and compared with that for a non-immersed formulation (control). Fluoroquinolone film-coated tablets were mixed with starch-based FTs, guar gum-based FTs, or XG-FTs to observe their appearances. Results The dissolution profile of LVFX film-coated tablets was not affected by XG-FTs, but the dissolution of TFLX and CPFX was delayed. For crushed film-coated tablets, the 15-min mean dissolution rate was significantly delayed for all three fluoroquinolones when compared with that of uncrushed products. The dissolution profile of TFLX film-coated fine granules was unchanged by XG-FTs. CPFX film-coated tablets and crushed products produced a gel-like precipitate when mixed with XG-FTs and failed to meet product-dissolution specifications. A gel-like precipitate was also observed with guar gum-based FTs. Conclusion The effect of XG-FTs on the dissolution profile of film-coated fluoroquinolone formulations varied depending on the formulation. The CPFX formulation formed a gel-like precipitate when immersed in XG-FTs resulting in a significantly delayed dissolution.